Nursing registries of educational actions for patients submitted to hip arthroplasty - Laiana Lauser Silveira; Miriam de Abreu Almeida; Marcos Barragan da Silva; Aline Tsuma Gaedke Nomura (Universidade Federal de Goias, 2015)
A retrospective, descriptive study of quantitative approach, aimed to identify nursing registries of educational actions for patients submitted to hip arthroplasty. The investigation was conducted in a university hospital in the South of Brazil, with a sample of 112 records from admitted patients. Data were collected through a checklist in June of 2013, and statistically analyzed. The educational registry was present in 60 (53%) records. Regarding the content, the post-surgery care 36 (53%), mobilization 23 (20,5%) and bed exit 21 (18,8%) were prevalent and were found in a total of 56 (50%) records on the Nursing Evolution document. Although nursing registries present aspects related to patient's education, better results could be obtained with the intervention operationalization, linked to nurse's permanent education.